1992
DOI: 10.1002/bit.260400813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymeric adsorbents on the production of sanguinarine by Papaver somniferum cell cultures

Abstract: The suitability of adsorbent polymeric resins, Amberlite XAD-4 and XAD-7 (Rohm and Hass, Inc.), was investigated for the accumulation of sanguinarine from Papaver somniferum cell cultures. The adsorption and desorption of sanguinarine from aqueous solution was most effective with XAD-7. In addition to sanguinarine, the resins were found to absorb growth regulators and vitamins from the culture medium. Growth inhibition was overcome by delaying for approximately 4 days resin addition after cell inoculation in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…As described by Brodelius and Pedersen (1993), transport of the secondary metabolites is redirected towards the extracellular space instead of being directed towards the vacuole, whose storage capacity limits alkaloid production. Results reported by Williams et al (1992) seem to support this hypothesis since the addition of extractive resins into cell suspensions reduced sanguinarine concentrations in both cells and medium by about 50%. However, in other cultures, the addition of an adsorptive phase did not substantially decrease cellular concentrations of alka- loids, despite increases in total production (Byun et al, 1990;Byun and Pedersen, 1994).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…As described by Brodelius and Pedersen (1993), transport of the secondary metabolites is redirected towards the extracellular space instead of being directed towards the vacuole, whose storage capacity limits alkaloid production. Results reported by Williams et al (1992) seem to support this hypothesis since the addition of extractive resins into cell suspensions reduced sanguinarine concentrations in both cells and medium by about 50%. However, in other cultures, the addition of an adsorptive phase did not substantially decrease cellular concentrations of alka- loids, despite increases in total production (Byun et al, 1990;Byun and Pedersen, 1994).…”
Section: Introductionsupporting
confidence: 74%
“…For example, Asada and Shuler (1989) reported a 67% increase in ajmalicine production with the addition of XAD-7 resins to Catharanthus roseus cultures, with 63% recovery on resins. Williams et al (1992) found that the addition of XAD-7 resins to Papaver somniferum cell cultures improved total sanguinarine production by 50 to 85%, with about 75% of the alkaloid recovered in the resin. A more recent report on the addition of XAD-7 to Catharanthus roseus showed that increase in production and the recovery of products were both dependant on the timing of the addition (Lee-Parsons and Shuler, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Cells were then cultured for 7 days in a production medium containing the elicitor and an extraction resin as recently described in Klvana et al (2004) (based on Archambault et al, 1996). An extractive resin was used to maximize production (Williams et al, 1992). Crude chitin (Sigma-Aldrich, Cat.…”
Section: Elicitability Testmentioning
confidence: 99%
“…In literature, the deleterious eect of resin addition at day 0 on cell viability has been attributed to the adsorption of essential hormones or vitamins from the medium (Robin and Williams et al, 1992). Williams et al (1992) reported that XAD-4 and XAD-7 resin can adsorb signi®cant levels of hormones and vitamins such as thiamin, kinetin, 2,4-dichlorophenoxyacetic acid, naphthalene acetic acid, and benzyladenine.…”
Section: Resin Capacity and The Adsorption Of Medium Componentsmentioning
confidence: 98%